Experimental investigation of a 250-kW turbine organic Rankine cycle system for low-grade waste heat recovery. Issue 14 (13th November 2016) - Fu, Ben-Ran; Lee, Yuh-Ren; Hsieh, Jui-Ching
ABSTRACT: An organic Rankine cycle (ORC) is generally used for converting low-grade heat into electricity. In this study, an extensive literature survey was conducted to identify current research gaps on experimental ORC systems. Specifically, there is limited experimental data and limited details on thermal and expander efficiencies of ORC systems. In order to address these gaps, the objective of this study included developing a turbine ORC with a power output exceeding 50 kW and thermal efficiency exceeding 8% for a heat source temperature < 120°C. The experimental results indicated that the system achieved a net power output of 242.5 kW and a thermal efficiency of 8.3% (the highest value for a turbine ORC system for the heat source temperature below 120°C). Thus, the study addressed the gaps identified in the research area of ORCs.